History as an afterthought: The (re)discovery of Article 18 in the case law of the European Court of Human Rights - Çalı, Başak; Hatas, Kristina (Edward Elgar Publishing Ltd., 2021)
This chapter investigates whether the recent heightened focus on Article 18, prohibiting restriction of rights for purposes not provided for in the European Convention on Human Rights, in the case law of the European Court of Human Rights is a return to the origins of the Convention, which identified Article 18 as ringing ‘alarm bells’ against the subtle progression of totalitarianism in Europe. We examine the development of the Article 18 case law of the Court by reviewing all publicly available cases that have pleaded Article 18 before the former Commission and the Court up until 2019. In light of this review, we find that the recent developments in the case law under Article 18 cannot be understood as returning to the origins of the Convention. It is a new development all together. We identify two reasons for the rediscovery of Article 18: the impetus to interpret the Convention progressively since its early days and the division amongst the bench of the Court as to how to interpret the drafting history of the Convention in current times.
CRIS-Team Scopus Importer:2023-03-21